An Exploration of the Application of Step Counter-Based Physical Activity Promotion Programs in Patients With Chronic Obstructive Pulmonary Disease: A Systematic Review - Han, Xiaoyu; Li, Peijun; Yang, Yahui; Liu, Xiaodan; Xia, Jun; Wu, Weibing (Frontiers in Public Health, 2021)
Objective: This paper aimed to systematically review the application methods and components of step counter-based physical activity (PA) promotion programs in patients with chronic obstructive pulmonary disease (COPD). The effects of longer-duration (≥12 weeks) programs on PA, exercise capacity, quality of life, and dyspnea were discussed. Methods: This review was performed in accordance with the preferred reporting items for systematic reviews and meta-analysis. Online data resources PubMed, Web of Science, Embase, and EBSCO were searched. The publication year was limited between January 2000 to August 2020. All randomized controlled trials with ≥12-week duration of step counter-based PA promotion programs of COPD were included. Two researchers independently assessed the quality of the included studies and extracted their characteristics. Results: Nine studies involving 1,450 participants were included. Step counters, counseling, exercise goals, diaries, and tele-communicational approaches were common components of these programs. The PA feedback tools were mostly pedometers (n = 8), whereas accelerometers were often used as assessment tools of PA (n = 5). All studies implemented counseling: five applied behavioral change theories, and three reported motivational interview techniques simultaneously. Six studies reported detailed exercise goals. The usual exercise goal was to reach a total of 8,000–10,000 steps/day. Three research studies used diaries, and five applied tele-communication approaches to deliver interventions. The programs could be implemented alone (n = 4), in combination with exercise training (n = 2), or with pulmonary rehabilitation (n = 2). All studies showed a significant increase in the PA (≥793 steps/day). Three studies observed a significant improvement in exercise capacity (≥13.4 m), and two reported a significant increase in the quality of life (p < 0.05). No study showed significant between-group differences in dyspnea. Conclusion: There are a few studies assessing the impact of long-duration (≥12 weeks) step counter-based interventions in COPD, with different methodologies, although all studies included counseling and exercise goal setting. These interventions seem to have a positive effect on PA. A few studies also showed benefit on exercise capacity and quality of life.